Copaifera langsdorffii Desf.: A chemical and pharmacological review. (January 2022) - Santos, Maria de Oliveira; Camilo, Cicera Janaine; Macedo, Julimery Gonçalves Ferreira; Lacerda, Maria Natália Soares de; Lopes, Cristiane Marinho Uchôa; Rodrigues, Antonio Yony Felipe; Costa, José Galberto Martins da; Souza, Marta Maria de Almeida
Abstract: The chemical composition of Copaifera langsdorffii Desf. is rich in sesquiterpenes and diterpenes, and is mainly indicated for healing and inflammation in general. Considering the medicinal importance of this species and the lack of research that gathers and analyzes the available information, this study aimed to verify if there is consensus on the medicinal use, chemical components and biological activities. A search was conducted in Pub Med, Science Direct, Scielo, Web of Science, Google Scholar and Institutional Repository of the Universidade Estadual Paulista. A total of 96 health problems were catalogued, of which inflammation in general and healing were the most cited, along with resin-oil and stem bark. Of the 277 compounds recorded, 91 were specific to the essential oil, 58 to the crude resin, and 57 to the extract. Caryophyllene oxide was the most frequent constituent. The major constituents presented variation in the essential oil, crude resin, extract and different parts of the plant. A total of 28 proven activities were recorded, of which the most tested were antioxidant, cytotoxic, anti-inflammatory and antibacterial. C. langsdorffii shows important sources of active principles in the combat of diseases which affect human health, mainly regarding the Skin, General, and Nonspecific systems. Its chemical composition is responsible for the biological activities demonstrated for the species. Further investigations are necessary, mainly regarding in vitro and in vivo pharmacological properties, isolation of substances, mechanism of action, and bioavailability, in order to provide subsidies for the development of new drugs. Graphical abstract: Image 1 Highlights: Copaifera langsdorffii has a high variability of therapeutic indications in different regions of Brazil. The essential oil and resin have unique compounds. Caryophyllene oxide is present in all types of extracts. Antioxidant, cytotoxic, anti-inflammatory and antibacterial activities were the most tested.